Biologia populacional de Imparfinis minutus (Siluriformes, Heptapteridae) na microbacia do Ribeirão Grande, serra da Mantiqueira oriental, Estado de São Paulo - de Moraes, Mariana Bissoli; Braga, Francisco Manoel de Souza [UNESP] (Universidade Estadual de Maringa, 2011)
Populational biology of Imparfinis minutus (Siluriformes, Heptapteridae) in the Ribeirao Grande microbasin, eastern Mantiqueira mountain range, São Paulo State. The aim of the work was to analyze biological aspects and distribution of Imparfinis minutus in the Ribeirao Grande microbasin (22[degree]4708[minute]''S, 45[degree]28[minute]17''W), in eastern Mantiqueira mountain range, from July 2001 to April 2002. Among the 37 species sampled, I. minutus (Siluriformes, Heptapteridae), was distributed from the piedmont to the plains of the Vale do Paraiba. The occurrence of this species was associated with the environments of small water volume, bottom with stones and gravel. The amplitude length of I. minutus was 4.75 to 12.75 cm. The length-weight relationship of the population was estimated at W = 0.0052 L3,13. Analyzing the alometric (Ka) and relative (Kr) condition factors, both indexes presented similar values. The lowest value was obtained in July, increasing gradually in October and January, and peaking in April. The analysis of the gonadossomatic relationship (GSR) of females showed higher values in July and January. The reproductive period of I. minutus occurred on spring/summer (October to January), as suggested by the gonadossomatic relationship and condition factor results. Feeding activity was constant, with fat visceral deposition concentrated in April and July. Imparfinis minutus is an aquatic insectivore opportunist species, consuming Diptera and Trichoptera larvae as secondary items. Most ingested food items were autochthonous resources.
Populational biology of Imparfinis minutus (Siluriformes, Heptapteridae) in the Ribeirao Grande microbasin, eastern Mantiqueira mountain range, São Paulo State.